SAFETY STOCKEFFICACIOUSNESSANALYSIS INFOODINDUSTRY (CASE STUDY: PT NIPPON INDOSARI CORPINDO TBK) - Leni Cynthia Dewi; Jessica Berta Joewono; Liem Gai Sin (AIBPM Publisher, 2018)
As the company grows, activities and problems become more complex. Problem about excess or lack of inventory have an important role to play in running the company, it is very difficult for the company leader to implement or coordinate directly. Appropriate policies are made to ensure continuity by using adequate internal management. The aim of this research is to know the implementation of handling product inventories, storage obstacle and the effort used to face the obstacle. This research is used to provide information for the company and gain knowledgefor the writers. The methods used in this journal are interview, documentation and literature study method. PT Nippon IndosariChorpindois one of the biggest food company with the main product “Sari Roti”. This company produces clean, healthy and qualified bread. Safety stock in the company is ruled by SAP system to inform the employees therefore the employees will know when they need to buy raw material. Keywords: Safety, Stock, Inventory, Sari Roti, Method, Management